Ischaemic Limb Changes in Patients with Peripheral Arterial Disease (PAD) Associated with Coronary Artery Disease (CAD) (University Heart Journal, 2012)
To correlate magnitude and distribution of coronary Artery Disease (CAD) with ischaemic limb changes in  patients with Peripheral Arterial Disease (PAD) of lower limbs.Most common cause of PAD is atherosclerosis.  Atherosclerosis is a generalized disease and often atherosclerotic CAD is associated with PAD. Because of  ischaemic limb changes in patient with PAD they do not always experience angina even after having CAD.  This prospective observational study was conducted in National Institute of cardiovascular Diseases (NICVD)  Dhaka, Bangladesh during July 2004 to June 2005. Total 58 patients with PAD were included in the study.  Patients were classified as group I having normal coronary artery, group-II insignificant CAD (L M